PENGARUH PENERAPAN PROBLEM-BASED LEARNING TERHADAP KEMAMPUAN SISWA DALAM MEMECAHKAN MASALAH MATEMATIS: STUDI META ANALISIS - Siti Barkah; Rafiq Zulkarnaen; Rika Mulyati Mustika Sari (Universitas Bhinneka PGRI, 2026)
The purpose of this study is to re-examine the impact of Problem Based Learning on students' mathematical problem-solving abilities with the help of Publish or Perish on the Google Scholar search engine for the last 10 years indexed by Sinta. This study uses meta-analysis in the form of descriptive qualitative analysis, which involves examining or evaluating research findings from published articles, with 25 national articles as samples. The filtered data were obtained from studies covering the number of experimental groups, the number of control groups, and t-tests. The summary effect size was then determined through meta-analysis of the data using the effect size value and standard error. Mathematical problem-solving ability is significantly influenced by the Problem-Based Learning model, according to the results of data analysis conducted using JASP software, with a value of 1.26 and an estimate of 1.257, which can be classified as very high. Thus, it can be concluded that the Problem-Based Learning model has a significant impact on students' ability to solve problem solving.